Ultra-low cycle fatigue fracture initiation life evaluation of thick-walled steel bridge piers with microscopic damage index under bidirectional cyclic loading. (September 2022) - Li, Shuailing; Lin, Jiahui; Zhuge, Hanqing; Xie, Xu; Cheng, Cheng
Abstract: Strong earthquakes can cause ultra-low cycle fatigue (ULCF) fracture in steel bridge piers. This paper examined the fracture behavior of two thick-walled square section steel bridge piers subjecting to horizontal bidirectional cyclic loading. In addition, a microscope damage index for evaluating ULCF fracture initiation life of steel bridge piers was proposed. The findings show that ductile cracking firstly appeared at the junction between the stiffened base plate and bottom weld at the corner position of steel bridge piers under bidirectional cyclic loading, and that initial crack growth did not reduce the strength capacity. The strength capacity of steel piers began to rapidly decline as cracks propagated into the base metal. The proposed microscope damage index for ULCF fracture initiation life evaluation of steel bridge piers performs well when compared to experimental and evaluation results.